Optimal interference of the tibial component of the cementless Oxford Unicompartmental Knee Replacement. Issue 3 (March 2018) - Campi, S.; Mellon, S. J.; Ridley, D.; Foulke, B.; Dodd, C. A. F.; Pandit, H. G.; Murray, D. W.
Abstract : Objectives: The primary stability of the cementless Oxford Unicompartmental Knee Replacement (OUKR) relies on interference fit (or press fit). Insufficient interference may cause implant loosening, whilst excessive interference could cause bone damage and fracture. The aim of this study was to identify the optimal interference fit by measuring the force required to seat the tibial component of the cementless OUKR (push-in force) and the force required to remove the component (pull-out force). Materials and Methods: Six cementless OUKR tibial components were implanted in 12 new slots prepared on blocks of solid polyurethane foam (20 pounds per cubic foot (PCF), Sawbones, Malmo, Sweden) with a range of interference of 0.1 mm to 1.9 mm using a Dartec materials testing machine HC10 (Zwick Ltd, Herefordshire, United Kingdom) . The experiment was repeated with cellular polyurethane foam (15 PCF), which is a more porous analogue for trabecular bone. Results: The push-in force progressively increased with increasing interference. The pull-out force was related in a non-linear fashion to interference, decreasing with higher interference. Compared with the current nominal interference, a lower interference would reduce the push-in forces by up to 45% (p < 0.001 One way ANOVA) ensuring comparable (or improved) pull-out forces (p > 0.05 Bonferroni post hoc test). With the more porous bone analogue, although the forces were lower, the relationship between interference and push-in and pull-out force were similar. Conclusions: This study suggests that decreasing the interference fit of the tibial component of the cementless OUKR reduces the push-in force and can increase the pull-out force. An optimal interference fit may both improve primary fixation and decrease the risk of fracture. Cite this article : S. Campi, S. J. Mellon, D. Ridley, B. Foulke, C. A. F. Dodd, H. G. Pandit, D. W. Murray. Optimal interference of the tibial component of the cementless Oxford Unicompartmental Knee Replacement. Bone Joint Res 2018;7:226–231. DOI: 10.1302/2046-3758.73.BJR-2017-0193.R1.